Circulation of Fungi of the Genus Candida in Children's and Adult Multi Purpose Hospitals - M. I. Petrukhina; A. M. Martynova2; N. G. Politova; N. V. Starostina; A. N. Cairo (Эпидемиология и вакцинопрофилактика, 2018)
The aim of the work is to study the circulation of fungi of the genus Candida in children's and adult multi purpose hospitals.Materials and methods. A total of 61,226 studies of material obtained from patients in the children's hospital were performed. A positive result was registered in 27 060 cases (44.2%). In an adult hospital, 8647 samples were tested, of which 1988 (23.0%) were positive.Results and discussion. Among the representatives of the fungi of the genus Candida, C. albicans 752 strains (61.3%) were isolated in the overwhelming number of patients of the children's hospital, C. papapsilosis – 15.1%, C. famata – 11.6%, and C. glabrata – 8.0%. Other representatives of the genus were rare enough, in particular: C. krusei and C. gullermondii – 1.1%, respectively. The greatest number of fungi of the genus – was allocated from patients in the Department of Resuscitation and Intensive Care – 467 strains (38.1% of all the fungi isolated), 186 strains (15.2%) in the Otorhinolaryngological department, 87 out of 87 (7.1%), in the Departments of Planned Surgery and Urology – 86 (7.0%), Surgical Intensive Care Unit – 72 (5.9%), in The Department of Infectious Diseases with Surgical Pathology – 65 (5.3%). C. albicans was sown both in monoculture – 47.4%, and in associations – 52.6%. Other representatives of fungi were also approximately equally found in mono- and in microcultures. In the children's multi purpose hospital, 11 species of Candida fungi with a predominance of C. albicans circulated. In the adult multi purpose hospital for two years was isolated from the patients 137 cultures of Candida fungi.Conclusions. The probability of isolating fungi from a locus is determined by the profile of the Department, as well as by the primary pathology with which patients entered the hospital. In both children's and adult hospitals, the most common Candida fungi have been isolated from the Department of Resuscitation and Intensive Care patients mainly from sputum and urine, less often from blood, separated wounds, abdominal cavity and from cerebrospinal fluid (only in children). Against the background of a wide circulation of fungi in the hospital, colonization of patients is possible with the subsequent development of the infectious process, mainly in people at risk.